Fine-Root Distribution and Soil Physicochemical Property Variations in Four Contrasting Urban Land-Use Types in South Korea - Lan Thi Ngoc Tran; Ji Young An; Mark Bryan Carayugan; Jonathan O. Hernandez; SK Abidur Rahman; Woo Bin Youn; Julia Inacio Carvalho; Min Seon Jo; Si Ho Han; Hai-Hoa Nguyen; Byung Bae Park (Plants, 2024)
Urbanization and associated forest conversions have given rise to a continuum of native (forest fragments) and modified (artificial grasslands and perennial ecosystems) land-use types. However, little is known about how these shifts affect soil and fine-root compartments that are critical to a functioning carbon and nutrient circulation system. In this study, soil physicochemical properties, fine-root mass, and vertical distribution patterns were investigated in four representative urban land-use types: grassland (ZJ), perennial agroecosystem (MP), broadleaf deciduous forest patch (QA), and coniferous evergreen forest patch (PD). We quantified the fine-root mass in the upper 30 cm vertical profile (0–30 cm) and at every 5 cm depth across three diameter classes (<2 mm, 2–5 mm, and <5 mm). Soil physicochemical properties, except for phosphorus, nitrogen, ammonium nitrogen, and sodium cations, varied significantly across land-use types. The total root biomass (<5 mm) decreased in the order of QA (700.3 g m−2) > PD (487.2 g m−2) > ZJ (440.1 g m−2) > MP (98.3 g m−2). The fine-root mass of ZJ and MP was correlated with soil nutrients, which was attributed to intensive management operations, while the fine-root mass of QA and PD had a significant relationship with soil organic matter due to the high inputs from forest litter. Very fine roots (<2 mm) presented a distinct decremental pattern with depth for all land-use types, except for MP. Very fine roots populated the topmost 5 cm layer in ZJ, QA, and PD at 52.1%, 49.4%, and 39.4%, respectively. Maintaining a woody fine-root system benefits urban landscapes by promoting soil stabilization, improving ground infiltration rates, and increasing carbon sequestration capacity. Our findings underscore the importance of profiling fine-root mass when assessing urban expansion effects on terrestrial ecosystems.